Gender and body side differences of glenoid morphometry - Md. Khadzari, Fadzillah (2015)

(untitled)
Background: Glenoid cavity orientation is crucial for the biomechanics of the glenohumeral joint. Reproducible data of the exact orientation and positioning of the glenoid cavity is important to evaluate various shoulder conditions. It is also useful as proper preoperative planning prior to replacement procedure and to minimize unfavourable implications of prosthetic failure. Among possible complications include prosthesis loosening, glenohumeral instability, tears of the rotator cuff, periprosthetic fracture, infection, neural injury, and dysfunction of the deltoid. The important parameters of glenoid morphometry are glenoid length, width, glenoid version and glenoid inclination. Aim of study: The aims of this study were to use multiplanar reconstructed CT images as the modality to determine the normal glenoid morphology among patients who underwent CT thorax in Hospital Universiti Sains Malaysia, to compare side and gender differences. Methods and Materials: This study was a cross sectional study. A total of 88 CT thorax were analyzed from 2009 to 2014 for non orthopaedic indications in Department of Radiology, Hospital Universiti Sains Malaysia (HUSM), Kubang Kerian, Kelantan. Results: A total of 176 glenoid cavities were measured. The mean glenoid length in male were 4.03cm (SD 0.28) and in female 3.45cm (SD 0.27). The mean for the glenoid width in male were 2.25cm (SD 0.23) and in female 1.95cm (SD 0.23).. The average glenoid version angle in male was 4.25 (SD 4.20) and in female was 4.97 (SD 5.41). The average glenoid inclination in male was 11.4 (SD 3.55) and in female was 8.77 (SD 4.26). There was significant difference in glenoid length and glenoid inclination between right and left scapula. However no significant difference observed in glenoid width and glenoid version between two sides. Significant difference also noted in mean value of glenoid dimension and glenoid inclination between male and female. However no significant difference reported in glenoid version of different gender. Conclusion: The dimensions of the glenoid observed in the present study were different from other studies done on other populations. The difference was found in glenoid length and inclination between right and left scapula. The glenoid dimension and inclination are significantly larger in male than female.